A pH Switch for β-Sheet Folding - Anderson, Jordan M. (Angew Chem Int Ed Engl, 2017)
Protein design advancements have led to biotechnological strategies based on more stable and more specific structures. Herein we present a 6-residue sequence (HPATGK) that acts as a stable structure-nucleating turn at physiological and higher pH but is notably unfavorable for chain direction reversal at low pH. When placed into the turn of a beta-sheet, this leads to a pH switch of folding. Using a standard 3-stranded β-sheet model, the WW domain, it was found that the pH switch sequence insertion caused minimal change at pH 8 but a ~50 °C drop in the melting temperature (T(m)) was observed at pH 2.5: ΔΔG(F) = >11.3 kJ/mol. Using the strategies demonstrated in this paper, the redesign of β-sheets to contain a global, or local, pH dependent conformational switch should be possible.